Beating Drug Tests and Defending Positive Results A Toxicologist's Perspective - Dasgupta, Amitava (Humana Press : Imprint: Humana, 2010)
A majority of the Fortune 500 Companies implement some practice of workplace drug testing in their company policies. This practice was first initiated by President Ronald Reagan when he ordered federal agencies to drug test federal employees involved in sensitive positions as well as positions involving public safety. As a practicing toxicologist, Dr. Amitava Dasgupta is involved with the pre-employment drug testing at his own hospital and aptly shares his expertise in Beating Drug Tests and Defending Positive Results: A Toxicologist's Perspective, which covers all major issues concerning how people try to beat drug tests and defend positive test results. In each chapter, extensive references are cited so that readers can access more information on a particular topic that may interest them. The book will undoubtedly prove helpful to toxicologists, medical technologists, pathologists, human resources professionals and anyone interested in workplace drug testing.